As críticas de Hegel às maneiras de se tratar o direito natural no período de Lena: a tragédia na vida ética - Loureiro Junior, William Paniccia [UNIFESP] (2019)
The purpose of this work is to present the review carried out by Hegel in The Scientific Ways of Treating Natural Law, published in 1801-1802. In the first place, will be addressed the philosophical view of Hegel as the Identity of the Identity and the non-identity or difference, highlighting his disagreement, mainly, to the philosophies of reflection, seeking to delimitate, in the originality of Jena, what the young German thinker understands for philosophy of speculation as a way to transcend the one-sided views of his philosophical predecessors. Posteriorly, over the next chapters, the analysis of the construction and development of de notion around the Tragedy of Ethical Life as a result of the relation that the ethical absolute plays with himself, namely, the imbricated relation of the negative that negates himself as a necessary part of the concrete position of the positive. Lastly, the exam of the perusal that Hegel does about the Orestes’ Trial, seeing in the tragedy The Eumenides of Aeschylus. Qualifying it as the best staged way to show the whole process of the ethical absolute, from his internal conflicts to his reconciliation as organized people itself and for himself.